Prevalence of age, gender and pathological conditions of vocal cords leading to hoarseness of voice in a tertiary care hospital - Rameshkumar, Edakkattil; Rosmi, Tony Kalliath (International Journal of Advances in Medicine, 2017)
Background: Voice disorders that affect children and adults have different causes with respect to different age groups. Factors associated with voice disorder ranges from the medical to emotional stress. This study was aimed to analyze the different pathological causes leading to hoarseness of voice in population attending a tertiary care hospital. Methods: Subjects with symptoms of hoarseness of voice visited the tertiary care hospital was included in the study. The etiologies such as vocal nodules, vocal cord polyps, vocal cord cysts, cancer of larynx, vocal cord paralysis and vocal cord oedema were evaluated using the video laryngoscopy. The prevalence was statistically analysed. Results: Ninety nine subjects of both gender (age 10-79 years) were included in the retrospective study. Among the total subjects, 51 subjects were males and 48 were females. Maximum prevalence of hoarseness was 41%, found in the age group of 50-79 years. The most common cause for the hoarseness was due to vocal nodule (22%), vocal polyp (19%) and cancer of larynx (17%). Number of subjects with the vocal nodule was significantly differ from that of vocal polyp (p =0.01, p<0.05). No significant difference (p>0.05) was found among the gender. However, the cancer of larynx was more associated with the age group 50-69 years with male dominance (p>0.05). Phonaesthenia was the minor cause (1%). Conclusions: Among the causes for the hoarseness of voice, vocal nodules were the major. Causes such as vocal cord polyps, laryngeal cancer, chronic laryngitis, were found in a descending order of prevalence.